2001
DOI: 10.1006/viro.2001.1168
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Analyses of Yellow Fever 17DD Vaccine Viruses Associated with Serious Adverse Events in Brazil

Abstract: The yellow fever (YF) 17D virus is one of the most successful vaccines developed to data. Its use has been estimated to be over 400 million doses with an excellent record of safety. In the past 3 years, yellow fever vaccination was intensified in Brazil in response to higher risk of urban outbreaks of the disease. Two fatal adverse events temporally associated with YF vaccination were reported. Both cases had features similar to yellow fever disease, including hepatitis and multiorgan failure. Two different lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 22 publications
1
57
1
5
Order By: Relevance
“…Viremia was checked in intermediate blood samples using tissue culture methods described elsewhere. 6 Analyses were conducted for the complete study cohort and for those who met all protocol requirements. The proportion of seroconversion, adverse events and abnormal values for liver enzymes, and the mean of antibody and enzyme levels were compared across comparison groups after immunization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viremia was checked in intermediate blood samples using tissue culture methods described elsewhere. 6 Analyses were conducted for the complete study cohort and for those who met all protocol requirements. The proportion of seroconversion, adverse events and abnormal values for liver enzymes, and the mean of antibody and enzyme levels were compared across comparison groups after immunization.…”
Section: Methodsmentioning
confidence: 99%
“…Severe events are rare and the association with the vaccine has been suggested by clinical and pathological evidence. 6,12,24 Although those reports did not lead to changes in immunization policies for YF, the WHO called for a revision of the safety of the vaccines. 26 The study assessed the immunogenicity and reactogenicity of a new seed lot prepared from one additional passage at Fundação Oswaldo Cruz (Fiocruz) in Brazil to replace the working seed.…”
Section: Introductionmentioning
confidence: 99%
“…So, it was concluded that the most probable explanation was individual susceptibility due to some unknown host factor. 10 The most baffling event was a cluster in space and time of 5 cases of YEL-AVD in Peru, of which 4 were confirmed cases, with the same lot, and intensive investigation yielded no abnormalities of the implicated vaccine lot and no common risk factors. 31 By now, there is no conclusive evidence that demonstrates that YEL-AVD is caused by increased virulence due to mutations in the genome of the YF 17D vaccine virus.…”
Section: Vaccine Virusmentioning
confidence: 98%
“…The limited number of genetic variations in the genome of the vaccine viruses and the lack of consistency of these changes when the genomes of case viruses are compared do not support single site reversion to wild type virus sequence, and therefore cannot explain the clinical picture. 10 All cases are first-time vaccinees. One underlying risk factor for YEL-AVD is thymectomy, 11 and old age also seems to be important, but evidence is conflicting across studies.…”
Section: Vaccine-associated Viscerotropicmentioning
confidence: 99%
“…É claro que os dados da história clínica e os antecedentes vacinais também são importantes e devem ser sempre valorizados 14 . Nos casos fatais em que não se dispõe de sangue para sorologia e a pesquisa de vírus foi negativa ou prejudicada, pode-se realizar a detecção de antígenos específicos por imunohistoquímica em tecidos hepáticos conservados em formalina tamponada 25 , ou detectar o genoma viral por RT-PCR do sangue (células e soro) e fígado, preservado sob refrigeração 11,[29][30][31] . Raramente outros tecidos se mostram positivos.…”
Section: Exames Específicos Exames Específicos Exames Específicos Exaunclassified